Dumbbell weight rack sensor - Rizalsham, Muhammad Afiq Zahran (2025)
This project addresses the common issue of gym goers failing to rerack dumbbells despite reminders and fines. Despite efforts such as posters and fines, some individuals continue to disregard the importance of reracking weights after use. The objective of this project is to educate gym goers about proper gym etiquette to create a more organized and convenient environment for all users. To achieve this, a buzzer system will be implemented to remind or slightly embarrass users who fail to rerack their weights correctly. This approach aims to encourage accountability and responsibility among gym goers. By making gym users feel like the space belongs to them, we think they'll be more likely to follow the rules about putting weights back where they belong. Consequently, the anticipated result is a noticeable improvement in weight placement, ensuring that the gym remains orderly and accessible to all. This project aims to create a friendly and helpful atmosphere at the gym, where everyone cares about each other. By teaching people, the right way to behave and making sure they follow the rules, we want to make the gym a happy place where everyone can work out without any problems. Overall, the implementation of this project aims to enhance the overall gym going experience for all participants, fostering a sense of community and mutual respect among users.